Postmortem Changes in pH, Color, Drip Loss, and Non-Protein Nitrogen in Beef Liver and Lungs During Storage in Refrigerator - Denny Lukman; Herwin Pisestyani; Hadri Latif; Etih Sudarnika; Mirnawati Bachrum (IPB University, 2020)
Beef offal are consumed by people in some countries specifically in Asia. Beef liver and lungs are favorite food which are used as meat in traditional food. The objective of this study was to determine the postmortem changes in pH, color, drip loss, and non-protein nitrogen (NPN) content in beef liver and lungs during storage in refrigerator (3-4 ºC) until 5 d (120 h) after slaughter. The beef liver and lungs were collected from the abattoir and transported in cool box (<7 ºC) to the laboratory within 3 hours. The samples size of beef liver and lungs were 20 for each observation time. In the laboratory the beef liver and lungs were measured directly for pH value, color (L*, a*, and b*), drip loss, and NPN content at 4 h postmortem (pm) and afterwards every beef liver sample was sliced into 5 pieces of 100-120 g and stored in chiller of 3-4 ºC. The measurement of pH, color (L*, a*, and b* values), drip loss, and NPN content were conducted at 4 h, 24 h, 48 h, 72 h, 96 h, and 120 h postmortem. Data were analyzed descriptively and by comparing the 95% confidence interval of mean of each observation. The results showed that pH, color, drip loss, and NPN content in beef lungs were higher than the values in beef liver. The pH of beef liver and lungs declines until 96 h pm and 48 h pm, respectively. The L*, a*, and b* values of beef liver and lungs increased in general during storage. Drip loss and NPN in beef liver and lungs tended to increase significantly during storage. From this study the pH value and NPN can be used to determine the freshness of beef liver and lungs.